Forecast combination approach with meta-fuzzy functions for forecasting the number of immigrants within the maritime line security project in Turkey - TAK, NİHAT (My University, 2023)
In this study, forecasting the number of immigrants on the Turkey\"s maritime line for use in a national security project carried out by Turkish Government within the scope of fight against uncontrolled immigration is discussed for the first time. Handling with the immigration problem is one of the biggest concerns of Turkey as unsupervised immigration can adversely affect the demographic and economic structure of the country. Precautions are needed as the short-, medium- and long-term impacts of undetected immigrants on the country\"s ecosystem are unpredictable, but due to the uncertainties inherent in immigration, the cost of using government resources such as patrol vehicles to capture undocumented immigrants can be extremely high. In order to both minimize the expenditure problem and keep immigration under control by providing a proper scan, forecasting the number of immigrants on the maritime line route is seen as an important problem and studied by probabilistic and non-probabilistic models. Since the data for 2020 and 2021 could not be attained yet due to COVID-19, in order to obtain forecasts and compare actual observations for 2019, which is the primarily focus of the research in this study, the dataset of interest on the number of daily immigrants between years 2016 and 2019 is obtained from Turkish Coast Guard Command within Ministry of Interior of Republic of Turkey. To obtain the most accurate forecasts, seven distinguished forecasting methods, from simple to complex, are implemented. Then, the forecast combination approach with meta-fuzzy functions which combines all methods is proposed. Consequently, the forecasting results are acquired and evaluated by using R. The evaluation of the results is made by using widely considered measurement accuracy metric root mean square error. According to the final assessments, the proposed approach gives more accurate forecasting results for the expected number of immigrants on the Turkey\"s maritime line and these results become an input to the national security project.
Keywords: Bilgisayar Bilimleri; Algoritmalar; Bilgisayar Grafiği; Mühendislik ve Teknoloji; Computer Sciences; algorithms; Computer Graphics; Engineering and Technology; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; Bilgisayar Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; COMPUTER SCIENCE; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; Yer Bilimlerinde Bilgisayarlar; Bilgisayarla Görme ve Örüntü Tanıma; Bilgisayar Bilimi Uygulamaları; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Yapay Zeka; Bilgisayar Bilimi (çeşitli); Genel Bilgisayar Bilimi; Fizik Bilimleri; Computers in Earth Sciences; Computer Vision and Pattern Recognition; Computer Science Applications; Computer Graphics and Computer-Aided Design; Artificial Intelligence; Computer Science (miscellaneous); General Computer Science; Physical Sciences; Immigration; Forecasting; Meta-fuzzy functions; Long short-term memory; Fuzzy inference systems and Artificial neural network; ARIMA; ANFIS; MODEL; ANN